Local Wisdom Values of Maumpan Tambang Tradition for Young Generation in Rantau Kalis Village Kapuas Hulu District - Dikawati, Margareta (International Journal Ethnic, Racial and Cultural Heritage, 2025)
This study examines the local wisdom values contained in the Maumpan Tambang Tradition in Rantau Kalis Village, Kapuas Hulu Regency. Maumpan Tambang is a ritual aimed at warding off disasters to protect the community from disturbances caused by supernatural beings believed to exist in the surrounding area. In the Dayak Kalis community of Rantau Kalis Village, Kapuas Hulu Regency, the Maumpan Tambang Tradition is observed once a year in mid-May. The Maumpan Tambang Tradition is a form of implementing traditional rituals that have deep meaning in the social, educational, and cultural life of the Dayak Kalis community. This study aims to identify and understand aspects of local wisdom values that are integrated into traditional rituals and their impact on cultural preservation and social harmony. The research method employed is a qualitative approach, utilising data collection techniques that include in-depth interviews, participatory observation, and document studies. The data analysis techniques used are data reduction, data presentation, and concluding. While the analysis in the study used five informants, namely one key informant and four supporting informants. The results of the study show that the Maumpan Tambang tradition contains important local wisdom values , such as cooperation and solidarity in society, cultural preservation, the preservation of tradition, and respect for ancestors. This tradition not only strengthens cultural identity but also serves as a mechanism to maintain ecological and social balance within the Dayak Kalis community. This study can contribute to the documentation and preservation of local wisdom values and increase understanding of the existence of traditions in contemporary society.